To the Discussion on Academic Philosophy: What, How, and What for - Elena A. Guseva; Marina I. Panfilova (Moscow Polytechnic University, 2019)
The article discusses how to implement common cultural competencies in the course of teaching philosophy. The authors believe that the optimal content of the course is the history of philosophy, which, when being creatively taught, can become a school of critical thinking and education and give direction to those who are trying to consciously shape their world view and educate their mind. The historical-philosophical approach organically incorporates the problematic one, makes it possible to discuss current issues of the day, based on classical examples of the philosophical culture. Some techniques for the development of cognitive skills that correspond to the strategies of liberal education are considered. The authors draw attention to the benefits of the work of a student with a philosophical text, the need for the development of written and oral speech, organically associated with the development of thinking. In the conditions of increasing bureaucratic regulation of the educational process and limited time, it is important to preserve the space of academic freedom, to build teaching taking into account the individual-personal contact with this or that audience. University philosophy is regarded as a valuable experience in overcoming the limitations of everyday consciousness, it seems to be a source of ideas that provides support in a situation of epistemological uncertainty and value relativism. The article covers both philosophical and theoretical, and applied aspects of the problem of teaching philosophy in higher education institution.